Rhythms of the heart: The history of electrophysiology and its current status in South Africa - Millar, Rob Scott; Chin, Ashley (SA Heart Journal, 2017)
The foundations of cardiac electrophysiology were laid in the 19th and 20th century by the elucidation of the anatomy and physiology of the conduction system and cardiac muscle. The development of the ECG by Einthoven in the early 1900s has been the basis for its clinical application and remains the most important tool for diagnosis of arrhythmias. Invasive electrophysiological studies have refi ned and added to this understanding and led to the development of catheter ablation of cardiac arrhythmias. The invention of pacemakers and implantable cardioverter defi brillators (ICDs) has revolutionised the treatment of patients with brady and tachyarrhythmias. Despite these advances, catheter ablation, pacemakers and ICDs are unavailable to the majority of patients living in sub-Saharan Africa. In South Africa, there is a paucity of electrophysiologists in the academic/public sector as almost all electrophysiologists serve patients with private health insurance.